Intestinal Dysbiosis in Subjects with Obesity from Western Mexico and Its Association with a Proinflammatory Profile and Disturbances of Folate (B9) and Carbohydrate Metabolism - Riggen-Bueno, Verónica; Del Toro-Arreola, Susana; Baltazar-Díaz, Tonatiuh Abimael; Vega-Magaña, Alejandra N.; Peña-Rodríguez, Marcela; Castaño-Jiménez, Paula Alejandra; Sánchez-Orozco, Laura Verónica; Vera-Cruz, José María; Bueno-Topete, Miriam Ruth (Metabolites, 2024)
Obesity is a public health problem with a growing prevalence worldwide. In Mexico, it is estimated that one out of three adults suffer from obesity. In these patients, the intestinal microbiota (IM) undergoes pathological changes that are associated with a dysbiotic state; however, the microbiota profile of adult subjects with obesity from western Mexico has not been described. To assess this, fecal samples were obtained from 65 participants (Obese = 38; Control = 27). The microbial composition was characterized by 16S rRNA amplicon sequencing. The IM of the group with obesity revealed a clear decrease in richness and diversity (p < 0.001), as well as a significant increase in proinflammatory bacterial groups, mainly genera belonging to the Negativicutes class, Escherichia/Shigella, and Prevotella. Likewise, an increase in short-chain fatty acid-producing bacteria was found, especially the genus Lachnoclostridium. Additionally, PICRUSt2 analysis showed a depletion of vitamin B9 metabolism and an increase in saccharolytic pathways. The IM of patients with obesity possesses a dysbiotic, proinflammatory environment, possibly contributing to lipogenesis and adiposity. Thus, assessing the IM will allow for a better understanding of the pathophysiology of metabolic diseases of high prevalence, such as obesity. These findings are described for the first time in the adult population of western Mexico.